Phasic and sustained brain responses in the amygdala and the bed nucleus of the stria terminalis during threat anticipation. Issue 3 (17th December 2015) - Herrmann, Martin J.; Boehme, Stephanie; Becker, Michael P.I.; Tupak, Sara V.; Guhn, Anne; Schmidt, Brigitte; Brinkmann, Leonie; Straube, Thomas
Abstract: Several lines of evidence suggest that the amygdala and the bed nucleus of the stria terminalis (BNST) are differentially involved in phasic and sustained fear. Even though, results from neuroimaging studies support this distinction, a specific effect of a temporal dissociation with phasic responses to onset versus sustained responses during prolonged states of threat anticipation has not been shown yet. To explore this issue, we investigated brain activation during anticipation of threat in 38 healthy participants by means of functional magnetic resonance imaging. Participants were presented different visual cues indicated the temporally unpredictable occurrence of a subsequent aversive or neutral stimulus. During the onset of aversive versus neutral anticipatory cues, results showed a differential phasic activation of amygdala, anterior cingulate cortex (ACC), and ventrolateral prefrontal cortex (PFC). In contrast, activation in the BNST and other brain regions, including insula, dorsolateral PFC, ACC, cuneus, posterior cingulate cortex, and periaqueductal grey was characterized by a sustained response during the threat versus neutral anticipation period. Analyses of functional connectivity showed phasic amygdala response as positively associated with activation, mainly in sensory cortex areas whereas sustained BNST activation was negatively associated with activation in visual cortex and positively correlated with activation in the insula and thalamus. These findings suggest that the amygdala is responsive to the onset of cues signaling the unpredictable occurrence of a potential threat while the BNST in concert with other areas is involved in sustained anxiety. Furthermore, the amygdala and BNST are characterized by distinctive connectivity patterns during threat anticipation. Hum Brain Mapp 37:1091–1102, 2016 . © 2015 Wiley Periodicals, Inc .